Recurrence Relations of K-Bessel’s Function: Kuldeep Singh Gehlot - Team, Support (Thai Journal of Mathematics, 2016)
In this paper we evaluate eight dierential recurrence relations and ve pure recurrence relations of K - Bessel function.